The Activation of PI3K/AKT/mTOR Signaling Pathway in Response to Cabazitaxel Treatment in Metastatic Castration-Resistant Prostate Cancer Cells - Işıl Ezgi Eryılmaz; Gamze Güney Eskiler; Ceyda Çolakoğlu; Ünal Egeli; Gülşah Çeçener (European Journal of Biology)
Objective: Despite advances in treatment approaches, metastatic castration-resistant prostate cancer (mCRPC) remains a clinical challenge to treat. Cabazitaxel (Cab), a third-line chemotherapy option for mCRPC, exhibits limited efficiency due to the activation of different signaling pathways associated with drug resistance. The PI3K/AKT/mTOR activation has led to mCRPC progression, and long-term acquired Cab resistance. However, we aimed to assess the association of apoptotic efficiency of Cab with the PI3K/AKT/mTOR activation in mCRPC cells in the present study. Materials and Methods: Cell viability, cell death, morphological analysis, PI3K/AKT/mTOR pathway activation by PI3K/MAPK dual activation assay, mRNA and miRNA expression analysis and immunofluorescence staining were performed in the Cabtreated PC3 cells. Results: Cab caused a significant reduction in PC3 cell viability and triggered apoptotic death at 1 and 5 nM for 72 h. Cab significantly induced PI3K/AKT/mTOR activation, and increased mRNA and activated protein levels of AKT and mTOR in PC3 cells, despite its increased apoptotic effect. Furthermore, the expressions of miR-205 and miR-579, the PI3K/AKT/mTOR targeted miRNAs, were upregulated after Cab treatment. Our findings have shown that the Cab treatment activated PI3K/ AKT/mTOR pathway is associated with its apoptotic effect in mCRPC cells. Conclusion: Although further studies are required to investigate the molecular mechanisms accompanying the Cab response in detail, the PI3K/AKT/mTOR activation, as an alteration related to the apoptotic effect of the drug, may play a role in Cab resistance in mCRPC cells, suggesting that combined therapy with PI3K/AKT/mTOR inhibitors may improve the Cab therapeutic efficiency.